Predators among protectors: overcoming power abuse during humanitarian crisis through effective humanitarian diplomacy and a gender-transformative approach - Sumbal Javed; Vijay Kumar Chattu; Hamid Allahverdipour (AIMS Press, 2021)
Sexual exploitation and abuse (SEA) is one of the most depraved crimes against humanity. When carried out by peacekeepers and humanitarian aid workers, it depicts a catastrophic failure of protection bringing harm to the very people the United Nations and international organizations vow to protect. This paper has highlighted the various allegations and incidents of SEA repeatedly happening in conflict-affected countries. Allegations of SEA have since surfaced related to operations in Bosnia, Cambodia, Somalia, Sierra Leone, Liberia, Kosovo, Cote d'Ivoire, Haiti, Sudan, Guinea and the Democratic Republic of Congo. The symptoms of abuse survivors generally resemble those of Post-Traumatic Stress Disorder, and SEA has significant health consequences and poses a severe threat to public health advancement. Based on the literature review, we propose that international and humanitarian organizations must ensure that these offences do not happen in the future by taking appropriate measures. These organizations must prioritize rigorous training on gender equality and values and include a basic mandatory test on gender equality before joining humanitarian missions. Since humanitarian diplomacy encompasses actions carried out by the humanitarian organizations to acquire space from military and political authorities within to function with integrity, we emphasize that strengthening humanitarian diplomacy can play a pivotal role to train the humanitarian workforce on best practices to reduce SEA. Besides, we further propose that women should be allowed to lead from the front; otherwise, true gender equality and issues relevant to gender, including SEA, will be challenging to attain.